Identifikasi potensi desa wisata tebing buatan (Waburi Park) Desa Gaya Baru, terhadap perubahan sosial-ekonomi masyarakat - Rujiman, La Ode Muhammad; Mansyur, Akhmad; Alimina, Naslina; Kabiruddin; Irunsah, Aslan (Universitas Halu Oleo, 2024)
The development of tourist villages can have positive and negative impacts on socio-economic changes in rural communities. Therefore, it is necessary to conduct research to identify the potential of tourist villages through the services and facilities of the Waburi Park artificial cliff ecotourism in Gaya Baru village. The purpose of the study was to identify the potential of tourist villages in Gaya Baru village through the development of the Waburi Park Artificial Cliff Tourism object towards socio-economic changes in the community. The study was conducted in December 2023 in Gaya Baru village, Lapandewa District, South Buton Regency. The research method used direct data collection in the field consisting of observation, observation, interview and documentation methods. Data were analyzed descriptively through primary data and secondary data. The results of the study showed that Gaya Baru Village has tourism potential consisting of Nature Tourism, Historical Tourism, Socio-Cultural Tourism, Artificial Tourism and Marine Tourism. The development of tourist villages into Waburi Park artificial cliff ecotourism through the Decree of the Regent of South Buton Number 464 of 2021. The management aspect of the Waburi Park Artificial Cliff Ecotourism is managed by BUMdes Permata Mandiri, Gaya Baru Village. The Ecotourism Management Aspect is managed by Pokdarwis Kamba Waburi. The increase in income of Gaya Baru village has a positive impact on the development of supporting facilities and infrastructure in the Waburi Park Artificial Cliff Tourism Object area. The development of the Waburi Park Artificial Cliff ecotourism destination can encourage socio-economic changes in the Gaya Baru village community by increasing village fund budget revenues from 2022 to 2023.